Comprehensive review of nanoparticles dispersion technology for automotive surfaces - Sharifah Norsakinah, Syed Zainal Abidin; Wan Hamzah, Azmi; Ramadhan, Anwar Ilmar; Nurul Nadia, Mohd Zawawi (Universitas Muhammadiyah Magelang, 2022)
Many innovations arose from the continual and thorough monitoring of overlooked characteristics of materials found in the environment. Automotive paints are always constantly exposed to a broad range of ambient temperature conditions, which reduces their longevity and encourages algae development. Through the effective incorporation of nanotechnology with this lotus effect, it has become possible to provide self-cleaning ability along with air purification and antibacterial performance to automotive surfaces like paint and coating. The addition of nanoparticles such as Titanium dioxide (TiO2) and Silicon dioxide (SiO2) helps to improve functionalities like water or stain resistance, ultra-violet protection, and scratch resistance. When the nanoparticles were added into paint, they degraded the polluting compounds on the material's surface by photo catalysis. Multiple photocatalytic functions and self-cleaning properties were observed in nanoparticles added to polyester acrylic paint. Therefore, this paper discussed the history of automotive painting, nanopaint technology, previous research on the method preparation, development, and current progress, the environmental health aspects of nanotechnology, as well as the performance in terms of automotive surfaces. The study discovered the requirements for nanoparticle dispersion and coating uniformity and appearance on automotive surfaces, which will serve as a benchmark for dispersion and coating methods for automotive surfaces.